Adapting to global environmental change in Patagonia: What role for disturbance ecology? - Veblen, Thomas (2011)
Research from the Patagonian-Andean region is used to explore challenges and opportunities related to the integration of research on wildfire activity into a broader earth-system science framework that views the biosphere and atmosphere as a coupled interacting system for understanding the causes and consequences of future wildfire activity. We examine how research in disturbance ecology can inform land-use and other policy decisions in the context of probable future increases in wildfire activity driven by climate forcing. Climate research has related recent warming and drying trends in much of Patagonia to an upward trend in the Southern Annular Mode which is the leading pattern of extratropical climate variability in the southern hemisphere. Although still limited in spatial extent, tree-ring fire history studies are beginning to reveal regional patterns of the top-down climate influences on temporal and spatial pattern of wildfire occurrence in Patagonia. Knowledge of relationships of fire activity to climate variability in the context of predicted future warming leads to the hypothesis that wildfire activity in Patagonia will increase substantially during the first half of the 21st century. In addition to this anticipated increase in extreme fire events due to climate forcing, we further hypothesize that current land-use trends will increase the extent and/or severity of fire events through bottom-up (i.e. land surface) influences on wildfire potential. In particular, policy discussions of how to mitigate impacts of climate warming on fire potential need to consider research results from disturbance ecology on the implications of continued planting of flammable non-native trees and the role of introduced herbivores in favouring vegetation changes that may enhance landscape flammability.